People of African Descent and COVID-19: Unveiling Structural Inequalities in Latin America - Economic Commission for Latin America; the Caribbean (United Nations, 2021)
COVID-19 (coronavirus) is exposing social inequalities of all kinds in the world and the region, as well as the overrepresentation of Afrodescendants among the group living in poverty who are employed in informal and caregiving jobs. As Afrodescendants have worse indicators of well-being than their non-Afrodescendent peers, they are seen as one of the groups most vulnerable to the COVID-19 pandemic, in terms of both infection and mortality. Accordingly, this document analyses the specific situation of Afrodescendent populations and the effects that COVID-19 might be having on them, based on up-to-date empirical dataand an ethnic/racial, generational, territorial, rights-based and gender approach.